Editorial: Urban Design – The Case of Bali - Cuthbert, Alexander R. (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 6 No 2 (2019): Oktober 2019DO - 10.24843/JRS.2019.v06.i02.p01, 2019)
-